Hydrothermal Pretreatment as a Strategy for the Improvement of Sugarcane Bagasse Saccharification by Fungal Enzyme Blend - Mariana Furtado Granato de Albuquerque; Tiago Ferreira Leal; Rafaela Inês de Souza Ladeira Ázar; Adriane Maria Ferreira Milagres; Valéria Monteze Guimarães; Sebastião Tavares de Rezende (Brazilian Archives of Biology and Technology, 2022)
Abstract Obtaining low cost lignocellulolytic enzymes and efficient biomass pretreatment are key to increase the competitiveness of second-generation ethanol in comparison with fossil fuels. The enzymatic cocktail produced by the Chrysoporthe cubensis fungus as well as the mixture prepared with the cocktails of the Chrysoporthe cubensis and Penicillium pinophilum fungi have already proven to be efficient for hydrolyzing biomass pretreated with alkali. In this study, they were evaluated in saccharification of sugarcane bagasse pretreated with dilute acid or hot water at 121°C using an enzyme loading equal to 8 filter paper units per gram of biomass. The most promising results were obtained from the hydrolysis of biomass pretreated with hot water by the C. cubensis-P. pinophilum enzymes blend. In this condition, the glucose and xylose production were 25.2 g.L-1 and 4.6 g.L-1, respectively, that resulted in the conversion of 68% of glucan and 23% of xylan in only 48 hours. This study shows that the hydrothermal pretreatment is a promising alternative to improve the enzymes performance, produced by the fungi C. cubensis and P. pinophilum, in the sugarcane bagasse hydrolysis without the need of chemical compounds, generally used in the acid and alkali pretreatments. Furthermore, the hydrothermal pretreatment for 60 min allowed all cocktails applied to convert the cellulose efficiently with only 24 h of saccharification, which contributes to the energy savings employed in the process.